Chronic alcohol administration alters metabolomic profile of murine bone marrow - Pontes Pereira, Tássia Tatiane; Fideles Duarte-Andrade, Filipe; Gardone Vitório, Jéssica; do Espírito Santo Pereira, Taiane; Braga Martins, Flavia Rayssa; Marques Souza, Jéssica Amanda; Malacco, Nathália Luisa; Mathias Melo, Eliza; Costa Picossi, Carolina Raíssa; Pinto, Ernani; Santiago Gomez, Ricardo; Martins Teixeira, Mauro; et al. (Frontiers in Immunology, 2023)
Introduction: People with hazardous alcohol use are more susceptible to viral, bacterial, and fungal infections due to the effect of alcohol on immune system cell function. Metabolized ethanol reduces NAD+ to NADH, affecting critical metabolic pathways. Here, our aim was to investigate whether alcohol is metabolized by bone marrow cells and if it impacts the metabolic pathways of leukocyte progenitor cells, leading to a qualitative and quantitative alteration of key metabolites which may be related to the immune response. Methods: We addressed this aim by using C57BL/6 mice under chronic ethanol administration and evaluated the metabolomic profile from bone marrow total cells by gas chromatography-coupled mass spectrometry (GC-MS). Results: We identified 19 metabolites. Our data demonstrated that chronic ethanol administration alters the metabolomic profile in the bone marrow resulting in a statistical diminished abundance of 5 metabolites in ethanol-treated animals: Uracil, succinate, proline, nicotinamide and tyrosine. Discussion: Our results demonstrate for the first time in literature the effects of alcohol consumption in the metabolome content of hematopoietic tissue and open a wide range of further studies in order to investigate mechanisms by which alcohol compromises the cellular function of the immune system.